EMed-opoly: Pediatric Fever - Andrew Phillips (Association of American Medical Colleges, 2014)
Abstract Introduction This is an electronic board game designed for use during residency education conferences. Questions apply to pediatric fever and are applicable to emergency medicine, pediatrics, and family medicine residents. The game incorporates interactive discussion, competitive pride, and academic society guidelines to provide both education and testing of pediatric fever topics. It is part of a series of topics based on the same game design. Methods Teams compete to own Emergency Department "rooms" (spaces) and race to answer questions during "codes." "Black Cloud" and "White Cloud" cards are intermixed to change the pace of the game and create a special opportunity for educators to customize the game for their residency program. Results The game was very well received anecdotally and by a post-game survey. Seventy four percent of residents and faculty reported learning the pediatric fever topic better with the game than traditional lecture. (Residents received two lectures on pediatric fever in the prior month to which they were asked to compare.) The pace was deemed appropriate to slightly slow with the die rolling most often cited as a cause of delay. Discussion The speed of the game is a critical component of success. The game requires constant pushing from the leader to ensure efficient time use. Additionally, the game was only trialed at one residency program, and success may not fully translate. Finally, slightly more preparation is required for this game with regard to logistics than a traditional lecture.